Methodology of special competences formation of the teacher of a foreign language under the conditions of inclusive education - Natalya A. Gridneva; Kseniya S. Oparina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Internationalization is one of the most important challenges of modern higher education, the main goal of which is the formation of a professionally-balanced personality.One of the main requirements for the successful entry of the Russian Federation (RF) into the educational space is the education of persons with disabilities. However, it is necessary to note the fact that this particular area is a lacunae in higher education. The most effective solution to the problem of training people with disabilities is inclusion, defined according to regulatory documents as the creation of all necessary conditions for students with special educational needs.Inclusion is carried out regarding the regulatory, financial, educational, methodological and psychological-pedagogical aspects. The latter aspect implies that the teacher has special competences to provide the necessary assistance for students with disabilities. However, today not all teachers have formed competences.The aim of the research is to assess the effectiveness of refresher courses (special competences) as a way of forming special competences for university teachers for psychological and pedagogical support of students with disabilities. In this study, we used a quantitative method and a survey of teachers of the department of linguistics, intercultural communication and Russian as a foreign at Samara State Technical University. After the entrance testing, the teachers had professional training courses, at the end of which we conducted the final control research. According to the results the students of the courses demonstrate higher degree of special competences development.